(untitled) (Research, Society and Development, 2021)
Purpose: To present the strategies used and the effects of early physiotherapy intervention using telehealth on a Down syndrome infant. Materials and methods: An infant diagnosed with Down syndrome performed the early intervention. Telehealth was performed synchronously according to the biopsychosocial model The assessments were carried out using the International Classification of Functioning, Disability and Health checklist. The Alberta Infant Motor Scale and the Brazilian version of the Affordances in the Home Environment for Motor Development - Infant scale were used to assess the activity component and environmental factors, respectively. Evaluations were performed at 5, 50, 79, and 105 days of corrected age. Results: The infant obtained progressive and constant gains during 100 days of early intervention. It is known that environmental and personal factors interfere with the performance of the infant’s skills. Conclusion: Early intervention initiated in the first month of life using telehealth in an infant with Down syndrome proved an effective intervention method.